2000
DOI: 10.1207/s15324826an0704_8
|View full text |Cite
|
Sign up to set email alerts
|

The Corsi Block-Tapping Task: Standardization and Normative Data

Abstract: This article describes a standardized administration and scoring procedure for the widely used Corsi Block-Tapping Task, designed to assess the visual memory span. This method was applied in a group of healthy participants (n = 70) and a group of patients with cerebral lesions (n = 70), that were categorized on the basis of lesion location (left or right hemisphere, bilateral or subcortical). The percentile distribution as well as cutoff points on the basis of the control data are provided. It was found that 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
574
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 797 publications
(600 citation statements)
references
References 5 publications
17
574
2
7
Order By: Relevance
“…Similarly, these positions were not always visible, unlike with the Corsi block task (see, e.g., Kessels, van Zandvoort, Postma, Kappelle, de Haan, 2000), making it more difficult to apply arbitrary verbal labels for each position (cf. Jones et al, 1995).…”
Section: Implications For the Understanding Of Auditory Attentional Cmentioning
confidence: 99%
“…Similarly, these positions were not always visible, unlike with the Corsi block task (see, e.g., Kessels, van Zandvoort, Postma, Kappelle, de Haan, 2000), making it more difficult to apply arbitrary verbal labels for each position (cf. Jones et al, 1995).…”
Section: Implications For the Understanding Of Auditory Attentional Cmentioning
confidence: 99%
“…Corsi Blocks A measure of short-term visuospatial memory that is sensitive to impairment (Kessels et al 2000). Jigsaw Puzzle An age sensitive measure of visuospatial memory with a retest reliability of .8918 (Richardson and Vecchi 2002).…”
Section: Visuospatial Memorymentioning
confidence: 99%
“…We used a computerized variation of the often-used Corsi block-tapping task (Corsi, 1972) to assess the participants' visuospatial memory (Kessels, van Zandvoort, Postma, Kappelle, & de Haan, 2000). During each trial of the visuospatial memory test, the participants were shown a grid of six-by-six squares on a computer screen and were asked to memorize a sequence of three to seven cued locations within this grid.…”
Section: Visuospatial Memory Taskmentioning
confidence: 99%